Endogenous money, liquidity and monetary reform - Sheila Dow (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
Following its revival in the 1980s, the idea of endogenous money became increasingly widely accepted. Indeed the 2008 global financial crisis was widely blamed on the untrammelled power of banks to create credit. As a result, among the ideas for reforming the monetary system are proposals designed to eliminate that power, that is, to make the money supply exogenous. The purpose of this paper is to go back to the theory of endogenous money in order to assess these proposals, in terms of what is desirable, but also crucially what is feasible. Central to this discussion is a consideration of the range of meanings given to money and endogeneity. It is argued that what is regarded as money under different conditions is an important element in money endogeneity, and is particularly relevant for the monetary reform debate.
Keywords: E4; E5; B2; B5; 330; Basil Moore; endogenous money; liquidity; monetary reform